Quantum Dot Molecules - Wu, Jiang; Wang, Zhiming M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
A quantum dot molecule (QDM) is composed of two or more closely spaced quantum dots or “artificial atoms.” In recent years, QDMs have received much attention as an emerging new artificial quantum system. The interesting and unique coupling and energy transfer processes between the “artificial atoms” could substantially extend the range of possible applications of quantum nanostructures. This book reviews recent advances in the exciting and rapidly growing field of QDMs via contributions from some of the most prominent researchers in this scientific community. The book explores many interesting topics such as the epitaxial growth of QDMs, spectroscopic characterization, and QDM transistors, and bridges between the fundamental physics of novel materials and device applications for future information technology. Both theoretical and experimental approaches are considered. Quantum Dot Molecules can be recommended for electrical engineering and materials science department courses on the science and design of advanced and future electronic and optoelectronic devices. Presents the first comprehensive reference focused solely on quantum dot molecules Provides state-of-the-art coverage of novel technologies and techniques Connects fundamental physical properties with device design Features contributions from worldwide leaders in the field.
Preface -- Chapter 1: Fabrication of semiconductor Quantum Dot Molecules: droplet epitaxy and local oxidation nanolithography techniques -- Chapter 2: InP Ring-Shaped Quantum Dot Molecules by Droplet Epitaxy -- Chapter 3: Optical properties of lateral InGaAs quantum dot molecules single- and bi-layers -- Chapter 4: Formation Principles and Exciton Relaxation in Semiconductor Quantum Dot - Dye Nanoassemblies -- Chapter 5: Polarization properties of multi-layer InAs quantum dot molecules as a function of their size -- Chapter 6: Analysis of reduced built-in polarization fields and electronic structure of InGaN/GaN quantum dot molecules -- Chapter 7: Interference single electron transistors based on quantum dot molecules -- Chapter 8: Quantum Interference Effects on the Electronic Transmission Through Quantum Dot Molecules -- Chapter 9: Phonon-assisted processes and spontaneous emission in double quantum dots -- Chapter 10: Förster resonant energy transfer signatures in optically driven quantum dot molecules -- Chapter 11: Stark effect and the measurement of electric fields with quantum dot molecules -- Index.
Keywords: Optical materials; Electronic materials; Quantum optics; Nanotechnology; Nanochemistry; Nanoscale science; Nanoscience; Nanostructures; Optical and Electronic Materials; Quantum Optics; Nanotechnology and Microengineering; Nanochemistry; Nanotechnology; Nanoscale Science and Technology